ATR-mediated proteome remodeling is a major determinant of homologous recombination capacity in cancer cells. Issue 16 (12th July 2018) - Kim, Dongsung; Liu, Yi; Oberly, Susannah; Freire, Raimundo; Smolka, Marcus B
Abstract: The ATR kinase is crucial for genome maintenance, but the mechanisms by which ATR controls the DNA repair machinery are not fully understood. Here, we find that long-term chronic inhibition of ATR signaling severely impairs the ability of cells to utilize homologous recombination (HR)-mediated DNA repair. Proteomic analysis shows that chronic ATR inhibition depletes the abundance of key HR factors, suggesting that spontaneous ATR signaling enhances the capacity of cells to use HR-mediated repair by controlling the abundance of the HR machinery. Notably, ATR controls the abundance of HR factors largely via CHK1-dependent transcription, and can also promote stabilization of specific HR proteins. Cancer cells exhibit a strong dependency on ATR signaling for maintaining elevated levels of HR factors, and we propose that increased constitutive ATR signaling caused by augmented replication stress in cancer cells drives the enhanced HR capacity observed in certain tumor types. Overall, these findings define a major pro-HR function for ATR and have important implications for therapy by providing rationale for sensitizing HR-proficient cancer cells to PARP inhibitors.